Analisis Perbandingan Hasil Tes Kemampuan Diferensial (TKD) dan Fingerprint Analysis dalam Mengukur Kecerdasan Logika Matematika dan Kecerdasan Verbal Linguistik pada Siswa SLTA - Wuri Prasetyawati; Rosemini Agoes Salim; Airin Yustikarini Saleh (Fakultas Psikologi Universitas Pancasila, 2014)
Analyzing human potential by using fingerprint analysis makes fingerprint analysis can be an alternative method to understand human potential. Before this trend became popular, psychological assessment is the best way to assess human ability for a certain purpose, such as selection, placement test, etc. There is a significant difference between those approaches that needed to be carefully studied, especially for fingerprint analysis. The accuracy of fingerprint analysis can reach to 90% even can figure out 13 weeks old babies' potentials. Scientifically there is no support evidence for this study. In psychology, there is a theory about human development that is not only determined by genetics. Environment brings great influence in determining psychological changes in human. This study focuses on the differences of the results between two approaches, conventional psychological assessment (TKD) and fingerprint analysis. In order to make this study to be more specific, this study will only examine two types of multiple intelligence, which are verbal linguistic and mathematical logic. The results of the study show that fingerprint analysis differs from TKD in assessing verbal linguistic intelligence but not in mathematical logic intelligence. Secondly, the result of fingerprint analysis in verbal-linguistic intelligence and mathematical logic are insignificant can predict actual condition that TKD has.